1993
DOI: 10.1007/bf00196919
|View full text |Cite
|
Sign up to set email alerts
|

Magic angle spinning 13C-NMR spin-lattice relaxation study of the location and effects of ?-tocopherol, ubiquinone-10 and ubiquinol-10 in unsonicated model membranes

Abstract: Abstract. e-Tocopherol, ubiquinone-10 and ubiquinol-10 have been studied by high resolution magic angle samples spinning 13C-nuclear magnetic resonance in egg yolk phosphatidylcholine multilamellar vesicles model membranes in order to assess their location and the induced perturbations on this model system. ~-Tocopherol is placed in such a position that it is in close contact with the head group of the phospholipid and exposed to the solvent. In this position it significantly perturbs the phospholipid head gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Therefore, the (TIM)-' values obtained for the different carbons in the PtdCho/cholesterol mixture should allow us to obtain relative distances to the phosphate group where the Gd3' is bound. Significantly, upon inclusion of cholesterol in PtdCho and in the presence of Gd", there were no PtdCho resonances broadened beyond detection, as was the case when a-tocopherol was inserted into model membranes (Salgado et al, 1993). In the last case, it was the result of the perturbation of the phospholipid induced by the presence of a-tocopherol in the upper part of the palisade structure of the bilayer.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, the (TIM)-' values obtained for the different carbons in the PtdCho/cholesterol mixture should allow us to obtain relative distances to the phosphate group where the Gd3' is bound. Significantly, upon inclusion of cholesterol in PtdCho and in the presence of Gd", there were no PtdCho resonances broadened beyond detection, as was the case when a-tocopherol was inserted into model membranes (Salgado et al, 1993). In the last case, it was the result of the perturbation of the phospholipid induced by the presence of a-tocopherol in the upper part of the palisade structure of the bilayer.…”
Section: Resultsmentioning
confidence: 91%
“…2). It is also interesting to compare the phospholipid nT, values in the presence of cholesterol with those obtained in the presence of a-tocopherol and coenzyme Q, both in the oxidized and in the reduced forms (Salgado et al, 1993). It was found that a-tocopherol ordered the head group and the acyl chain of the phospholipid, whereas the molecule of coenzyme Q, in its two forms, slightly disordered the acyl chain of the phospholipid.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Both molecules are anchored at the aqueous interface by an OH group [11,30,31] have rigid rings at mid-structure and a branched chain protruding into the membrane interior. Admittedly, the amount of a-tocopherol in membranes is usually considerably less than cholesterol (such as in plasma membranes), but perhaps not in others, such as in the late endosome/lysosome [32,33].…”
Section: A-tocopherol and Pufa: Complexation Versus Associationmentioning
confidence: 99%